Impact of nasal septal perforation on the airflow and air-conditioning characteristics of the nasal cavity - Yang Na; Kyung Won Kwon; Yong Ju Jang (Scientific Reports, 2024)
Abstract We investigated (1) how nasal septal perforations (NSPs) modify nasal airflow and air-conditioning characteristics and (2) how the modifications of nasal airflow are influenced by the size and location of the NSP. Computed tomography scans of 14 subjects with NSPs were used to generate nasal cavity models. Virtual repair of NSPs was conducted to examine the sole effect of NSPs on airflow. The computational fluid dynamics technique was used to assess geometric and airflow parameters around the NSPs and in the nasopharynx. The net crossover airflow rate, the increased wall shear stress (WSS) and the surface water–vapor flux on the posterior surface of the NSPs were not correlated with the size of the perforation. After the virtual closure of the NSPs, the levels in relative humidity (RH), air temperature (AT) and nasal resistance did not improve significantly both in the choanae and nasopharynx. A geometric parameter associated with turbinate volume, the surface area-to-volume ratio (SAVR), was shown to be an important factor in the determination of the RH and AT, even in the presence of NSPs. The levels of RH and AT in the choanae and nasopharynx were more influenced by SAVR than the size and location of the NSPs.